Respuesta :

Answer:

r - 24

Step-by-step explanation:

[X · Y - Z] = (r + 2)(2r - 9)] - (r^2 + 17r + 30)

= (2r^2 + 4r - 9r - 18 ) - r^2 - 17r - 30

= 2r^2 - 5r - 18 - r^2 - 17r - 30

= r^2 - 22r - 48

= (r +2)(r - 24)

so

[X · Y - Z] / X

= [(r +2)(r - 24)]  /  (r + 2)

= r - 24

gmany

Answer:

r - 24

Step-by-step explanation:

Use PEMDAS:

P Parentheses first

E Exponents (ie Powers and Square Roots, etc.)

MD Multiplication and Division (left-to-right)

AS Addition and Subtraction (left-to-right)

================================================

[tex]X=r+2,\ Y=2r-9,\ Z=r^2+17r+30[/tex]

[tex][X\cdot Y-Z]\div X[/tex]

First: the product X · Y:

[tex](r+2)(2r-9)[/tex]     use FOIL (a + b)(c + d) = ac + ad + bc + bd

[tex]=(r)(2r)+(r)(-9)+(2)(2r)+(2)(-9)\\\\=2r^2-9r+4r-18=2r^2+(-9r+4r)-18\\\\=2r^2-5r-18[/tex]

Second: the difference X · Y - Z:

[tex]2r^2-5r-18-(r^2+17r+30)=2r^2-5r-18-r^2-17r-30\\\\=(2r^2-r^2)+(-5r-17r)+(-18-30)\\\\=r^2-22r-48[/tex]

Third: the quotient [X · Y - Z] ÷ X:

[tex](r^2-22r-48)\div(r+2)=\dfrac{r^2-22r-48}{r+2}=\dfrac{r^2+2r-24r-48}{r+2}\\\\=\dfrac{r(r+2)-24(r+2)}{r+2}=\dfrac{(r+2)(r-24)}{r+2}[/tex]

cancel r + 2

[tex]=r-24[/tex]